Transactions, Volume, and Volatility - Jones, Charles M.; Kaul, Gautam; Lipson, Marc L. (Review of Financial Studies, 1994)
We show that the positive volatility-volume relation documented by numerous researchers actually reflects the positive relation between volatility and the number of transactions. Thus, it is the occurrence of transactions per se, and not their size, that generates volatility; trade size has no information beyond that contained in the frequency of transactions. Our results suggest that theoretical research needs to entertain scenarios in which (1) both the frequency and size of trades are endogenously determined, yet (2) the size of trades has no information content beyond that contained in the number of transactions. Article published by Oxford University Press on behalf of the Society for Financial Studies in its journal, The Review of Financial Studies.